An Integrated Approach to the Treatment of Severe Psoriasis: A Clinical Case - Lyudmila Smirnova (Journal of Global Pharma Technology, 2020)
Psoriasis is a disease of autoimmune origin, affecting not only the skin, but also the internal organs of a person. Currently, many methods of treating psoriasis are in use, which vary in effectiveness. The aim of this work is to analyze the results of complex physiotherapeutic and pharmacological treatment of a patient with severe psoriasis in comparison with the initial failed treatment with traditional pharmacological methods. The therapy was carried out in 2018-2019 (observation by a rheumatologist at the place of residence), after treatment that was unsuccessfully carried out in 2016 at the Institute of Rheumatology (Federal State Budget Scientific Institution